2015
DOI: 10.1515/bmc-2014-0039
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic considerations of the APOE gene

Abstract: Abstract:The apolipoprotein E (APOE) gene is robustly linked with numerous physiological conditions, including healthy aging, altered cardiovascular fitness, and cognitive function. These connections have been established primarily by phenotype-genotype association studies using APOE's three common genetic variants (ε2, ε3, and ε4). These variants encode for the three apoE protein isoforms (E2, E3, and E4), which have slightly different structures and, consequently, distinct functions in lipid metabolism. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…APOE ε4 bears two CG dinucleotides mediated by rs429358 (minor allele) and rs7412 (major allele) that reside in the CpG island of exon 4 (Fig. 5 ) [ 18 , 28 ]. rs769450 does not affect CG content (Table 2 ), while rs440446, the first target haplotype SNP meditates the CG dinucleotide arisen by minor allele, similar to the last ones,.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…APOE ε4 bears two CG dinucleotides mediated by rs429358 (minor allele) and rs7412 (major allele) that reside in the CpG island of exon 4 (Fig. 5 ) [ 18 , 28 ]. rs769450 does not affect CG content (Table 2 ), while rs440446, the first target haplotype SNP meditates the CG dinucleotide arisen by minor allele, similar to the last ones,.…”
Section: Resultsmentioning
confidence: 99%
“…Its relatively rapid expansion could be attributed to converging to meat diet in ancient human populations [ 30 ]. The data suggest also that specific APOE haplotypes might have protective effect against AD development potentially via epigenetic reprogramming of APOE due to CpG emergence/dropout [ 18 , 28 ]. Altogether, our data demonstrated that ethnic genetic background defines significant differences in haplotypes for AD- risk alleles in human populations that may potentially be additional factor modifying risk for AD.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the two single nucleotide polymorphisms (SNPs) that define the ε2/ε3/ε4 alleles of APOE are both CpG dinucleotide altering, such that the ε4 allele introduces an additional CpG site in an already CpG-dense region (i.e., four CpGs within 12 bp) compared to the ε3 and ε2 alleles. In contrast, the ε2 allele eliminates one CpG site to open up a 33-bp CpG-free region compared to the ε3 and ε4 alleles (Yu and Foraker, 2015). Whether such a difference in the epigenetic code can lead to diverse epigenetic changes and contributes to the differential AD risks associated with the ε2/ε3/ε4 alleles is currently under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the exon 4 region of APOE that encompasses the ε 2/ ε 3/ ε 4 allele variants, is also a well-defined CGI [12]. Furthermore, the two ε 2/ ε 3/ ε 4 allele-defining SNPs (rs429358 and rs7412) are both CpG-altering and amend the CpG content of this CGI.…”
Section: Introductionmentioning
confidence: 99%